2020
DOI: 10.1007/s13304-020-00781-y
|View full text |Cite
|
Sign up to set email alerts
|

An underestimated “false negative COVID cholecystitis” in Northern Italy and the contagion of a surgical ward: it can happen everywhere

Abstract: A 45-year-old healthy woman was admitted to our Emergency Department (ER) with severe abdominal pain in the right abdominal quadrant and high fever. Blood test showed elevated levels of white blood cells (17,700 per ml) and high C reactive protein level (24,802 mg/ml [range 0-5]), while procalcitonin level was normal. Abdominal ultrasound revealed an acute cholecystitis with no free fluid in the abdomen. Temperature was 37.9° Celsius (C) at admission. The patient was then admitted to our Surgical Department an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Cholecystectomy is one of the commonest abdominal surgeries performed worldwide. To date, there are several reports of COVID-19 patients undergoing cholecystectomy, including our institution's experience [3][4][5][6]. Taking into account current available evidence, we provide some recommendations for performing cholecystectomy safely in suspected, presumed or confirmed COVID-19 patients.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Cholecystectomy is one of the commonest abdominal surgeries performed worldwide. To date, there are several reports of COVID-19 patients undergoing cholecystectomy, including our institution's experience [3][4][5][6]. Taking into account current available evidence, we provide some recommendations for performing cholecystectomy safely in suspected, presumed or confirmed COVID-19 patients.…”
mentioning
confidence: 97%
“…It was previously suggested that a pre-operative chest X-ray and nasopharyngeal swab should be performed for all elective procedures. However, with better understanding that pre-symptomatic viral transmission can occur [12] and nasopharyngeal swab results may be negative in the initial phase of disease [4], these measures alone may not be sufficient. In our institution, we call our patients 72 hours prior to surgery to ensure that they have no acute respiratory illness or recent travel history [2,11].…”
mentioning
confidence: 99%